A tabu search algorithm for the heterogeneous fixed fleet vehicle routing problem - Brandão, José (2011)
In the heterogeneous fixed fleet vehicle routing problem there are different types of vehicles and a given number of vehicles of each type. The resolution of this problem consists of assigning the customers to the existing vehicles and, in relation to each vehicle, defining the order of visiting each customer for the delivery or collection of goods. The objective is to minimize the total costs, satisfying customers’ requirements and visiting each customer exactly once. In this paper a tabu search algorithm is proposed and tested on several benchmark problems. The computational experiments show that the proposed algorithm produces high quality solutions within an acceptable computation time. Four new best solutions are reported for a set of test problems used in the literature.